The impact of Ready-to-Use Supplementary Food (RUSF) in targeted supplementation of children with moderate acute malnutrition (MAM) in South Africa - Liana Steenkamp; Ronette Lategan; Jacques Raubenheimer (South African Family Practice)
Objective: To describe catch-up growth in children with moderate acute malnutrition (MAM) on targeted supplementation using Ready-to-Use Supplementary Food (RUSF).